The microRNA processing subunit DGCR8 is required for a T cell-dependent germinal center response - Daum, Patrick; Ottmann, Shannon R.; Meinzinger, Julia; Schulz, Sebastian R.; Côrte-Real, Joana; Hauke, Manuela; Roth, Edith; Schuh, Wolfgang; Mielenz, Dirk; Jäck, Hans-Martin; Pracht, Katharina (Frontiers in Immunology, 2022)
We have previously shown that the microRNA (miRNA) processor complex consisting of the RNAse Drosha and the DiGeorge Critical Region (DGCR) 8 protein is essential for B cell maturation. To determine whether miRNA processing is required to initiate T cell-mediated antibody responses, we deleted DGCR8 in maturing B2 cells by crossing a mouse with loxP-flanked DGCR8 alleles with a CD23-Cre mouse. As expected, non-immunized mice showed reduced numbers of mature B2 cells and IgG-secreting cells and diminished serum IgG titers. In accordance, germinal centers and antigen-specific IgG-secreting cells were absent in mice immunized with T-dependent antigens. Therefore, DGCR8 is required to mount an efficient T-dependent antibody response. However, DGCR8 deletion in B1 cells was incomplete, resulting in unaltered B1 cell numbers and normal IgM and IgA titers in DGCR8-knock-out mice. Therefore, this mouse model could be used to analyze B1 responses in the absence of functional B2 cells.